PROPOSED MARKETING STRATEGI OF BAVERAGE BRAND CASE STUDY SMILKE (The Indonesian Journal of Business Administration, 2019)
The low level of milk consumption in Indonesia is a challenge and also opportunity. Smilke took this business opportunity in this field. Smilke is a beverage brand that focus on milk products released on March 2019. At this stage,Smilke focuses on increasing sales and branding so that the Smilke product can be known by targeted segment. Therefore Smilke requires the right marketing strategy so that the business plan can run. Quantitative methodology used in order to gather information regarding internal and external environment of Smilke. Internal analysis tools used are resource analysis, value chain anlysis and STP to identify Smilkes strengths and weaknessess. External analysis tools used are five force Porter, competitor and customer analysis to identify opportunities and threats that facing by Smilke. Based on the result analysis, the solution is Smilke should do benchmarking and develop some attributes including 7P in marketing mix. Strategies that can be carried out by Smilke in 2 years, which is finding mixologist to create product differentiation and add new variants, design eye catching packaging, expand more branch, campaign of drinking milk, endorsement and more promotion. These strategies is to achieve Smilke goals that increase sales and brand awareness.Keywords: Marketing Strategy, Beverage brand, Internal analysis, external analysis, Marketing Mix